Observatório do esporte: uma abordagem diferenciada no jornalismo esportivo no rádio - Pessoa, Rodrigo Turati [UNESP] (2012)
This project aims to analyze and understand the extension project called Observatório do Esporte, and especially, the radio program Observatório do Esporte, aired weekly on Rádio Unesp FM that reached the 100th edition in October 2012. Constructed on a research of structure and style of the program, based on eleven chosen editions, this project tries to identify regularities and changes during the almost three years of existence, as well as their linking with the original project configuration to which it is linked and which has as its main objective the realization of a differentiated thematic approach in relation to sports journalism commonly practiced in the media